Letter from Bert Betts to Jane Tolmach - Bert A. Betts:::::: (1960)
A message to Tolmach stating that they have a list of Democratic county Central committee Chairmen already issued. And is congratulating her for contribution to the county committee and will be there to support her in any way he can.